Campion: Debugging Router Configuration Differences - Tang, Alan; Kakarla, Siva Kesava Reddy; Beckett, Ryan; Zhai, Ennan; Brown, Matt; Millstein, Todd; Tamir, Yuval; Varghese, George (ACM SIGCOMM 2021, 2021)
We present a new approach for debugging two router configurations that are intended to be behaviorally equivalent. Existing router verification techniques cannot identify all differences or localize those differences to relevant configuration lines. Our approach addresses these limitations through a _modular_ analysis, which separately analyzes pairs of corresponding configuration components. It handles all router components that affect routing and forwarding, including configuration for BGP, OSPF, static routes, route maps and ACLs. Further, for many configuration components our modular approach enables simple _structural equivalence_ checks to be used without additional loss of precision versus modular semantic checks, aiding both efficiency and error localization. We implemented this approach in the tool Campion and applied it to debugging pairs of backup routers from different manufacturers and validating replacement of critical routers. Campion analyzed 30 proposed router replacements in a production cloud network and proactively detected four configuration bugs, including a route reflector bug that could have caused a severe outage. Campion also found multiple differences between backup routers from different vendors in a university network. These were undetected for three years, and depended on subtle semantic differences that the operators said they were "highly unlikely" to detect by "just eyeballing the configs."